The association between dietary patterns and the prevalence of mental health among university students / Syaidatul Afiqah Yusof … [et al.] - Yusof, Syaidatul Afiqah; Ismail, Zulkifli; Ismail, Ahmad Dzulkarnain; Mohd Rosli, Norfaezah; Mansor, Siti Hannariah; Jamaludin, Masshera (Universiti Teknologi MARA, Perlis, 2023)
Certain dietary habits may have an impact on mental health. Many studies have shown that diet affects how the body regulates mood by influencing the release of neurotransmitters, but there are conflicting results when it comes to young adults. The aim of the present study is to determine dietary patterns and its relationship with mental health status in among university students. This study was conducted in the form of a cross-sectional analytical observation at UiTM Perlis. A total of 362 students provided the data using two types of questionnaires. The Food Frequency Questionnaire (FFQ) was used to assess dietary patterns, and the General Health Questionnaire (GHQ-12) was used to assess mental health status. Results showed a high prevalence of irregular dietary patterns and mental health status in the sample. The Spearman correlation test revealed that there was no association between dietary habits and mental health status. Results also indicated that 71.3% of the students had a score below four, implying good mental health. However, 28.7% of the students were classified as having poor mental health. Our study highlights the irregularities in food intake among university students, most of whom had inadequate intakes of the recommended amounts. Therefore, the higher institution should perform studies on interventions to cope with changing dietary habits among students. However, their mental health portrayed status of good condition. This could be due to other factors that contribute to the occurrence of mental illness, including physiological, psychological, and social factors. These findings can be used by institutions to promote proper nutrition for this study population.